Sustainability Reporting : Moderating The Impact of Financial Performance on Stock Price - Rosilawati, Linda; Nawirah (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to examine the influence of financial performance on stock prices with sustainability reports as a moderating variable. Financial performance is measured through four categories. Sustainability reports are measured using the GRI-G4 index. The research population includes 27 palm oil industry companies listed on the Indonesia Stock Exchange. The research sample consists of 17 palm oil industry companies that consecutively disclosed annual reports, financial reports, and sustainability reports from 2018 to 2022, using purposive sampling. The data analysis method in this study involves panel data regression and Moderated Regression Analysis (MRA) using Eviews 12 software. The test results indicate that earnings per share and net profit margin have a significant impact on stock prices. However, the current ratio and debt-to-equity ratio do not influence stock prices. Meanwhile, sustainability reports can moderate the impact of earnings per share, net profit margin, and current ratio on stock prices but cannot moderate the impact of the debt-to-equity ratio on stock prices.